If f(x)=1/9x-2, what is f-1(x)?

NetherCraft 0

I’m so confused. Can somebody please explain to me..

Answer choices are .

f-1(x)=9x+18

f-1(x)=1/9x+2

f-1(x)=9x+2

f-1(x)=-2x+1/9

2 Answers

  • Assuming: f(x) = (1/9)x – 2

    y = (1/9)x – 2

    9y = x – 18

    x = 9y + 18

    f^(-1)(y) = 9y + 18

    f^(-1)(x) = 9x + 18

  • It is vital that questions be presented in the proper manner.

    Brackets MUST be used.

    Having to take a GUESS at :-

    y = f (x) = (1/9) x – 2

    (1/9)x = y + 2

    x = 9y + 18

    g (y) = 9y + 18

    g (x) = 9x + 18________inverse function.

Also Check This  Is Smirnoff strong???

Leave a Reply

Your email address will not be published. Required fields are marked *